2018
DOI: 10.4236/jmmce.2018.66043
|View full text |Cite
|
Sign up to set email alerts
|

Cure Characteristics and Mechanical Properties of Pineapple Leaf Fibre Filled Natural Rubber

Abstract: The cure characteristics and mechanical properties of natural rubber filled with pineapple leaf fibre (PLF) were studied at different filler contents and particle sizes. The PLF was characterized for filler properties while carbon black (N330) served as the reference filler. The natural rubber vulcanizates were compounded on a two-roll mill. Results showed that PLF (300 µm) filled natural rubber vulcanizates exhibited the highest maximum torque (T max) (47.04 lb-in) at filler content, 10 phr among the filler p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In other words, the viscosity increases when the filler contents increase. Good fillerto-matrix adhesion is shown by the rise in 𝑀𝑀 𝐿𝐿 with greater filler content, which limits the free mobility of rubber chains [22]. Similar observation had been reported by Justyna Miedzianowska et al, [23].…”
Section: Cure Characteristicssupporting
confidence: 72%
See 1 more Smart Citation
“…In other words, the viscosity increases when the filler contents increase. Good fillerto-matrix adhesion is shown by the rise in 𝑀𝑀 𝐿𝐿 with greater filler content, which limits the free mobility of rubber chains [22]. Similar observation had been reported by Justyna Miedzianowska et al, [23].…”
Section: Cure Characteristicssupporting
confidence: 72%
“…𝑡𝑡 𝑠𝑠2 of the prepared NR compounds shows a decrease in trend up to 20 phr and slightly increase at 30 phr of PALF content. The decrease of 𝑡𝑡 𝑠𝑠2 with greater fibre content may be owing to fibre-related factors such as fibre surface reactivity, fibre surface area, and fibre particle size [22].…”
Section: Cure Characteristicsmentioning
confidence: 99%
“…The present paper which is an extension of a previous report [19] presents results obtained on the end-use properties of pineapple leaf fibre filled natural rubber. The pineapple leaf fibre (PLF) sieved to 75, 150 and 300 µm particle sizes was used within filler contents, 0 to 40 phr.…”
Section: Introductionmentioning
confidence: 63%
“…The properties of the rubber vulca-nizates investigated were abrasion resistance, hardness, swelling index and specific gravity. In an earlier communication [19], PLF was used to compound natural rubber and the study showed that pineapple leaf fibre enhanced the tensile, flexural, compression strengths and tensile modulus of the natural rubber vulcanizates whereas the elongation at break of the unfilled natural rubber vulcanizate was greater than those of filled rubber vulcanizates. In Nigeria, pineapple leaves presently have no identifiable industrial applications and can be seen littering farm yards as wastes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation